The Effect Artificial Intelligence Based Discovery Learning Model on Student Creative Thinking Skills - Erizar, Erizar; Mustamin, Kaso; Purwantini, Purwantini; Halim, Abdul; Santosa, Tomi Apra (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to determine the effect of artificial intelligence-based discovery learning models on students' creative thinking skills. This research is a type of meta-analysis research. The data source comes from the analysis of 12 national and international journals. Search for data sources via Google Scholar, ProQuest, ScienceDirect, and Plos ONE. Inclusion criteria in this research are published articles from national and international journals indexed by SINTA and Scopus. The research was published from 2016-2023. The research has an experimental class with a discovery learning model and a control class with a conventional model. The research has a sample size of > 20 students. The research results concluded that the summary effect size or mean effect size value was 0.851 , a high criterion. These findings show that the artificial intelligence-based discovery learning model has an influence on students' creative thinking skills.